Mistletoe, moussaka, and murder - Kashian, Tina (Kashian, Tina. Kebab Kitchen mystery, 2020)
"Not even her impending nuptials can keep Lucy Berberian, manager of her family-owned Kebab Kitchen, from the Jersey Shore's annual Polar Bear Plunge. But her dive into the icy ocean is especially chilling when she finds a fellow swimmer doing the dead man's float for real ... Who would kill a man in cold blood during Ocean Crest, New Jersey's most popular winter event? When Lucy learns the victim is Deacon Spooner, the reception hall owner who turned up his nose and his price at her wedding plans, she can't help wondering who wouldn't kill the pompous caterer ... Perhaps the culprit is the wedding cake baker whose career Deacon nearly destroyed or the angry bride whose reception he ruined. With her maid of honor, Katie, busily planning Lucy's wedding without her, Lucy will have to get to the bottom of this cold-hearted business in time for Kebab Kitchen's mouthwatering Christmas celebration and before her hometown's holiday spirit washes out to sea."--Provided by publisher.